Late quaternary sedimentation in the Balearic basin - ΤΣΑΛΚΙΤΖΗ Ο.; ΑΝΑΣΤΑΣΑΚΗΣ Γ. (Bulletin of the Geological Society of Greece, 2018)
A detailed sedimentological study has been performed on five long piston cores recovered from the Balearic Abyssal Plain, the largest plain in the Mediterranean Sea. All the cores were dominated by multiple turbidite sequences, most of them displaying pronounced upward fining. The presence of a megaturbidite bed representing a single depositional event is observed in all the cores. Biostratigraphic correlation of the interlayered pelagic beds, using a high resolution nannofossil zonal scheme, suggests that the sediments in the cores date back to 50-100kyrs BP and that the age of the megabed is less than 50kyrs BP. The sedimentation rates for the last 50kyrs (over 50cm/Kyr) are greater in the northern and central Balearic Plain as compared to the lower sedimentation rates of 40cm/Kyr in the southern margin of the plain. Sedimentation rates (9,7-13,4cm/Kyr) are significantly reduced in the time interval between 50-120kyrs. The emplacement of the megaturbidite and the minor turbidites coincide with the sea level low stands. During these periods, great part of the continental shelf was revealed and processes sush as erosion, transportation and position became more intense.